WDR20 Regulates Activity of the USP12·UAF1 Deubiquitinating Enzyme Complex - Kee, Younghoon (American Society for Biochemistry and Molecular Biology, 2010)
The UAF1 (Usp1-associated factor 1) protein binds and stimulates three deubiquitinating enzymes: USP1, USP12, and USP46. Although the USP1·UAF1 complex is required for regulation of the Fanconi anemia (FA) DNA repair pathway, less is known about the USP12·UAF1 and the USP46·UAF1 complexes. To understand further the nature of the USP12 and USP46 complexes, we attempted to identify proteins that interact with the USP12 and USP46 deubiquitinating enzyme complexes. We identified WDR20, a WD40-repeat containing protein, as a common binding partner of UAF1, USP12, and USP46. Further analysis showed that WDR20 associates exclusively with USP12 and USP46, not with USP1. Furthermore, we demonstrate the purification of a ternary USP12·UAF1·WDR20 complex. Interestingly, and consistent with the binding assays, WDR20 stimulated the enzymatic activity of USP12·UAF1, but not of USP1·UAF1. Consistent with our previous report that USP12 and USP46 do not regulate the FA pathway, small interference RNA-mediated depletion of WDR20 protein did not affect the FA pathway or DNA damage responses. We provide a model in which WDR20 serves as a stimulatory subunit for preserving and regulating the activity of the subset of the UAF1·USP complexes.